Classification of episiotomy: towards a standardisation of terminology - Kalis, V; Laine, K; de Leeuw, J W; Ismail, K M; Tincello, D G (BJOG, 2012)
Seven episiotomy incisions are described in the literature, although only midline, mediolateral or lateral episiotomies are commonly used. Recent research has demonstrated variations in both site and direction of the incision, and differences between the angle of incision at the time of crowning of the fetal head and the angle of the scar once the wound has been repaired. We review this evidence and suggest that this variation may undermine the reliability of much published work. We suggest a standardised definition of each type of episiotomy to establish uniformity going forward, so that future studies are amenable to comparison and meta-analysis.
Keywords: anální kanál; medicína založená na důkazech; terminologie jako téma; rizikové faktory; epiziotomie; Obstetric Labor Complications; ženské pohlaví; Evidence-Based Medicine; Anal Canal; Humans; Pregnancy; Female; Risk Factors; komplikace porodu; těhotenství; Episiotomy; lidé; Terminology as Topic